Effect of Negative Pressure Therapy on the Inflammatory Response of the Intestinal Microenvironment in a Porcine Septic Model - Kenneth C. Norbury; Mary Pat Moyer (Mediators of Inflammation)
In a swine model of ischemia/reperfusion injury coupled with sepsis, we have previously shown attenuation of secondary organ injury and decreased mortality with negative pressure therapy (NPT). We hypothesized that NPT modulates the intestinal microenvironment by mediating the innate immune system. Sepsis was induced in 12 anesthetized female pigs. Group 1 (n=6) was decompressed at 12 hrs after injury (T12) and treated with standard of care (SOC), and group 2 (n=6) with NPT for up to T48. Immunoparalysis was evident as lymphocytopenia at T24 in both groups; however, survival was improved in the NPT group versus SOC (Odds ratio = 4.0). The SOC group showed significant reduction in lymphocyte numbers compared to NPT group by T48 (p<0.05). The capacity of peritoneal fluid to stimulate a robust reactive oxygen species response in vitro was greater for the NPT group, peaking at T24 for both M1 (p=0.0197) and M2 macrophages (p=0.085). Plasma elicited little if any effect which was confirmed by microarray analysis. In this septic swine model NPT appeared to modulate the intestinal microenvironment, facilitating an early robust, yet transient, host defense mediated by M1 and M2 macrophages. NPT may help overcome immunoparalysis that occurs during inflammatory response to septic injury.